Solvothermal synthesis of grain size controlled nanocrystalline SnO2 - 徐刚 徐盛明 陈崧哲 吴芳 李林艳 (Transactions of Nonferrous Metals Society of China, 2006)
Uniform nanocrystalline SnO2 with different particle sizes was prepared by a solvothermal method using SnCl4·5H2O as the starting material and ethanol as the solvent in the presence of different concentrations of HCl or KOH. The as-prepared powders were characterized by X-ray diffraction（XRD）, transmission electron microscopy（TEM）, thermo-gravimetry and differential thermal analysis（TG-DTA）, and nitrogen BET measurements. With increasing alkalinity of the precursor solution, the crystallite size of the as-prepared SnO2 nanocrystals decreases from 7.1 nm to 3.2 nm, while the specific surface area of the as-prepared powders increases from 101 m^2/g to 195 m^2/g. When calcined at 500 ℃ for 2 h in air, the crystallite size of the as-calcined powders increases slightly （12-5.9 nm） and the specific surface area of the as-calcined powders is 42-63 m2/g.